The secreted form of a melanocyte membrane-bound glycoprotein (Pmel17/gp100) is released by ectodomain shedding - Hoashi, Toshihiko (The Federation of American Societies for Experimental Biology, 2010)
Ectodomain shedding is a proteolytic mechanism by which a transmembrane protein is converted into a secreted form. Pmel17/gp100 is a melanocyte-specific membrane-bound glycoprotein that has amyloid characteristics and forms fibrillar structures in melanosomes after a complex sequence of post-translational processing and trafficking events, including cleavage by a furin-like proprotein convertase (PC). A secreted form of Pmel17 (termed sPmel17) was also thought to be released due to cleavage by a PC. We used multidisciplinary approaches to demonstrate that sPmel17 is released by ectodomain shedding at the juxtamembrane and/or intramembrane motif and to show that this is independent of cleavage by a PC. We further show that sPmel17 consists of 2 fragments linked by disulfide bonds and that the shedding is inhibited at low temperature but not by metalloproteinase inhibitors. Moreover, treatment with a phorbol ester or a calmodulin inhibitor induces Pmel17 shedding. We also refine the reactivity of HMB50 and NKI/beteb, 2 monoclonal antibodies commonly used as melanoma-specific markers. The fact that those antibodies require physically separated domains of Pmel17 sheds interesting light on its 3-dimensional conformation. We conclude that sPmel17 is released by regulated proteolytic ectodomain shedding.—Hoashi, T., Tamaki, K., Hearing, V. J. The secreted form of a melanocyte membrane-bound glycoprotein (Pmel17/gp100) is released by ectodomain shedding.